Psychological insulin resistance in type 2 diabetes patients: a cross-sectional study at a tertiary care hospital in Islamabad, Pakistan - Mohammad Ali Arif; Fibhaa Syed; Ayesha Javed (Journal of the Pakistan Medical Association, 2026)
Objective: To assess psychological insulin resistance, and to identify associated factors among type 2 diabetes patients. Methods: The cross-sectional study was conducted at the Pakistan Institute of Medical Sciences, Islamabad, Pakistan, between August 2023 and January 2024, and comprised type 2 diabetes patients. Apart from routine demographic and clinical data, Insulin Treatment Appraisal Scale scores were collected to evaluate the participants’ attitudes towards insulin therapy. Data were analysed using SPSS 25. Results: Of the 397 patients with mean age 47.22±15.04 years, 201(50.6) were females and 196(49.4) were males. The mean Insulin Treatment Appraisal Scale score was 34.58±7.75, indicating a moderately resistant attitude towards insulin therapy. Concerns about insulin use were prevalent, with 136(34.3%) participants agreeing that insulin initiation signified a failure in managing diabetes through diet and tablets, and 148(37.3%) having a fear of needles. The Insulin Treatment Appraisal Scale score had significant associations with marital status, monthly income, education level and certain comorbidities (p<0.05). Conclusion: The level of psychological insulin resistance was found to be considerable among type 2 diabetes patients, emphasising the need for targeted patient education. Key Words: Type 2 diabetes mellitus, Psychological insulin resistance, Insulin Treatment Appraisal Scale, Diabetes management.